(3WQjb GdhUhd Edi Yde GdCUhds - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj egO bhGYO bhGfjf Ojfg GdMfja HJaUjdg aUhd eYGde TQYg GdTQja (B... (3PcQhG gh Yde HbhGYO (B.. (3dGSJfHGW LRjFGJ GdCMcGe GdeJQJHI YdjgGs
(3BNQgG (B:s
(3BNQgG(B: (3aj ebGe GdTc hGdMjQI Ydi Cf jbJVj GdUd GdHQFI ef GdJcdja HeG Od Ydjg hdjS dCMO Cf jJeSc HGdHQGFI ef eDOj GdNjQ GdehGab (B... (3hGddg GdYGde hBNQ bhdfG GdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B15: 123s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs